A 27 YEARS OLD WOMAN WITH SEVERE PREECLAMPSIA AND PARTIAL HELLP SYNDROME - Annida Nurul Haq (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Preelampsia and HELLP Syndrome are one of emergency case in obstetric, which is characterized by hypertension and proteinuria after 20 weeks gestation, where HELLP Syndrome is presence of hemolysis, elevated liver enzymes, and low platelets. A case report taken at October 2013 in Abdul Moeloek general hospital. Primary data way obtained from anamnesis and physical examination. Secondary data was from laboratorium examination and medical report. A 27 years old, fullterm pregnancy, G2P1A0, came todelivering with history of hypertension since 32 weeks gestacy, the laboratorium examination is thrombocytes 147.000/mm3, LDH 644 u/l, and urinary excretion of 5gr protein in a 24-hour specimen (4+ reading on dipstick). The management of this patient is including fluid management, preventing eclampsia, management of blood pressure and corticosteroid. Precise management in this case prevents advance complication and decrease mothers mortality rate. [J Agromed Unila 2014; 1(3):232-237]Keywords: HELLP syndrome, hypertension in pregnancy, preeclampsia, severe preeclampsia